Optimizing the Function of Palembang City Forest as a Natural Laboratory - Angraini, Erni; Auliandari, Lia; Dewiyeti, Susi (Universitas PGRI Semarang, 2023)
Urban forest is one of the public open spaces with a minimum area of 2,500 m2(0.25 hectares) which has various functions, both ecological, social and cultural, economic, and aesthetic functions. Each urban forest has its own potential and function. The urban forest in Palembang has not been used optimally in accordance with its function, especially as a learning space (natural laboratory). This research aims to optimize the function of urban forests in Palembang so that they can be used as natural laboratories in Plant Ecology courses. The method in this study uses a qualitative approach with applied research. Data collection techniques include (triangulation techniques), including: observation on 6 urban forests in Palembang: Punti Kayu Natural Tourism Park Forest, Bukit Siguntang Forest, Bumi Perkemahan Pramuka Gandus City Forest, Forest Area of Sri Mulyono Herlambang Palembang Air Base, OPI Retention Pool Area, and Jakabaring Stadium Area; Interview; and documentation. Based on the results of field observations and interviews with the six urban forests in Palembang, they have various functions including ecological, social and cultural functions, as well as aesthetics. Urban forests that have low biodiversity are the Gandus Scout Campground City Forest and the OPI Retention Pond Area Forest. The Urban Forest of the OPI Retention Pool Area and the City Forest of the Gandus Scout Camping Ground have no potential to be used as natural laboratories, especially in the Ecology course on vegetation analysis material. There needs to be good cooperation from the government, the industrial world, and the community to optimize the function of urban forests.